Biofilm's double-edged resilience: A critical review of the environmental and clinical paradox in the one health nexus - Awaluddin, Muhammad; Sumayyah, Ishmah (EcoVision: Journal of Environmental Solutions, 2026)
Background: The microbial biofilm, a matrix-encased community, represents a foundational biological entity mediating critical outcomes across both environmental and human health sectors. The purpose of this comprehensive review is to synthesize the disparate literature on biofilm dynamics and its dual impact, thereby establishing the necessary framework for a unified research strategy. A vast body of work confirms the biofilm's role in nutrient cycling and protection, but simultaneously highlights its involvement in major global challenges, including infectious disease and ecological stability loss. Methods: This review synthesizes extant literature from environmental microbiology, clinical medicine, and biogeochemistry to construct a cohesive theoretical model. The core theoretical component introduced is the "biofilm health" analogy, which compares a biofilm community to an ecosystem where functional diversity dictates resilience and resistance to invasion. Findings: The core finding is the biological paradox inherent in the biofilm's structure: the same resilience mechanism (the Extracellular Polymeric Substance, or EPS) that drives positive ecological processes like bioremediation simultaneously accelerates the global crisis of Antimicrobial Resistance (AMR) in clinical settings, and facilitates the persistence of environmental pathogens and destructive biocorrosion. This paradox mandates a holistic research paradigm shift. Conclusion: Addressing this paradox necessitates a unified One Health approach, compelling researchers to develop non-antimicrobial disruption strategies targeting the EPS matrix. Novelty/Originality of this article: This work introduces the "biofilm health" analogy as a transdisciplinary conceptual tool and provides the first comprehensive synthesis detailing how the biofilm structure itself acts as the central bottleneck linking ecological stability and clinical health outcomes.